60.6k views
3 votes
Solve this system of equations.

2x + 6y = −6,

4x − 3y = −12


What is the solution to the system of equations?

(
,
)

2 Answers

5 votes

Answer:

-3,0

Step-by-step explanation:

edge 2021 assingment for last lesson

User Dorin Botan
by
5.4k points
3 votes

Answer:

(-3, 0)

Step-by-step explanation:

(Just wanted to give you a heads up that you posted this under the English category.)

We can solve this system by elimination. Let's multiply the first equation by two and keep the second equation the same to get the same first term:

4x + 12y = -12

4x - 3y = -12

We can now subtract the two equations to isolate the y term:

4x - 4x = 0

12y - (-3y) = 15y

-12 - (-12) = 0

We then get the equation: 15y = 0

Solve for y by diving both sides by 15; we get y = 0.

Now we can choose either equation in the system and plug in y, and then solve for x:

2x + 6(0) = -6

2x = -6

x = -3

Our answer is (-3, 0).

We can also check our answer by plugging it in the other equation:

4(-3) - 3(0) = -12

-12 - 0 = -12

Since this equation is true, our answer is correct and solves this system.

User Odetta
by
4.9k points